The Impact of Brand Awareness on Trust Perceived Risk, Satisfaction and Loyalty in Dining Restaurant: Case Study, North Cyprus - Geraldine, Ebong Emoke (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This research in tend to explore the effect of brand awareness on trust perceived risk satisfaction and fidelity in dining restaurant. Restaurant service has a significant role with regards to customer experience which could led to satisfaction and as such ,Brand awareness has a significant role in customer’s contentment and customer allegiance in dining restaurant industries wherein clients risk more for purchasing which is actually categorized and expensive than other restaurant. (Nitiwanakul, 2014). Trust is seen as a mediating factor between the dependent (Brand Awareness) and independent variable (Satisfaction and Loyalty), this variable exist so that there will be the uncertainty of the customer could be reduced. (Jana, Tracey and Greg, 2013). Hence when customers perceive such positive evaluation it will cause satisfaction leading to loyalty. (Maizura, 2016). This study’s purpose is to apprehend in what ways brand awareness has impacted on clients satisfaction and allegiance, more over this study aims at investigating how restaurant service act as an element which contribute to customer experience, this study is significant in that it gives a clear understanding pertaining to how customers react to a brand they are aware of which could cause satisfaction leading to customer loyalty. Based on the methodology a quantitative technique of data collection was utilized in this study to understand how each component has an effect on the other.

ÖZ: Araştırmanın amacı restoranlarda marka farkındalığının; güven, algılanan risk, tatmin ve sadakat üzeriner etkisini ölçmektir. Restoran hizmetlerinin tüketici tecrübesi ve tatmini üzerine olan etkisi ve restoran işletmelerinde marka farkındalığının tüketicinin satın alma davranışlarına olan etkisi bu araştırmanın dar alanını oluşturmaktadır. Araştırma sonuçlarına göre güven, marka farkındalığı ve tüketici tatmini ve sadakati üzerinde etkiye sahiptir. Bu sonuca göre tüketicilerde markaya karşı olan güvenin derinleştirilmesi ve tüketicilerin zihinlerindeki belirsizliklerin giderilmesi marka farkındalığı açısından son derece önem arz etmektedir. Bu sonuç doğrultusunda bir diğer ilişkide tatminin sadakat düzeyini arttırdığıdır. Çalışmanın metodolojisini kantitatif yöntemler oluşturmuştur. Korelasyon ve regresyon yoluyla ilişkiler test edilmiştir. Toplanan veriler SPSS 12.1 programında analiz edilmiştir.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Supervisor: Assist. Prof. Dr. Rüçhan Kayaman.
Keywords: Tourism; Tourism--Restaurants--Cyprus, North); Restoran hizmeti; Marka bilinirliği; Güven; Algılanan risk; memnuniyet; ve baglike; Restaurant service; Brand Awareness; Trust; Perceived Risk; Satisfaction; loyalty